Single‐pill combination of cilnidipine, an l‐/n‐type calcium channel blocker, and valsartan reduces the day‐by‐day variability of morning home systolic blood pressure in patients with treated hypertension: A sub‐analysis of the HOPE‐combi survey. Issue 2 (17th January 2021) - Kario, Kazuomi; Matsuda, Saori; Nagahama, Shinobu; Kurose, Yoshiki; Sugii, Hitoshi; Teshima, Tsukasa; Suzuki, Noriyuki
Abstract: We examined the effects of a fixed‐dose single‐pill combination of cilnidipine (10 mg), an L‐/N‐type calcium channel blocker, and valsartan (80 mg) (SPC of Cil/Val) on the day‐by‐day variability of morning home systolic blood pressure (MHSBP) in 616 patients with treated hypertension for 12 months as a sub‐analysis of the HOPE‐Combi survey, multicentral, post‐marketing, and prospective observational survey. The SPC of Cil/Val was administrated once a day in the morning. The SPC of Cil/Val decreased the standard deviation (SD, from 6.3 ± 4.8 to 5.1 ± 3.8 mmHg, p  < .01), coefficient of variation (from 4.3 ± 3.2 to 3.8 ± 2.9%, p  < .05), average real variability (ARV, from 7.9 ± 6.6 to 6.3 ± 5.1 mmHg, p  < .01), and the difference between maximum and minimum (MMD, from 11.9 ± 9.2 to 9.7 ± 7.2 mmHg, p  < .01) of MHSBP. The variability of MHSBP increased with age; however, this was not increased in patients ≥70 years at the baseline. In elderly patients (≥70 years, N  = 283), the SPC of Cil/Val decreased the SD (from 6.9 ± 5.6 to 5.6 ± 4.4 mmHg, p  < .01), ARV (from 8.6 ± 7.7 to 6.9 ± 5.7 mmHg, p  < .05), and MMD (from 13.2 ± 10.7 to 10.7 ± 8.3 mmHg, p  < .01) of MHSBP at 12 months; the reduction in these MHSBP variability parameters was comparable to that in adults <70 years. These results suggest that the SPC of Cil/Val is effective in reducing day‐by‐day variability of MHSBP in elderly patients.